Inhibition of TYK2 and JAK1 Ameliorates Imiquimod-Induced Psoriasis-like Dermatitis by Inhibiting IL-22 and the IL-23/IL-17 axis - Works, Melissa G. (2014)
Psoriasis is a chronic autoimmune disease affecting the skin and characterized by aberrant keratinocyte proliferation and function. Immune cells infiltrate the skin and release proinflammatory cytokines that play important roles in psoriasis. The Th17 network, including IL-23 and IL-22, has recently emerged as a critical component in the pathogenesis of psoriasis. IL-22 and IL-23 signaling is dependent on the JAK family of protein tyrosine kinases, making Janus kinase (JAK) inhibition an appealing strategy for the treatment of psoriasis. Here we report the activity of SAR-20347, a small molecule inhibitor with specificity for JAK1 and Tyrosine Kinase 2 (TYK2) over other JAK family members. In cellular assays, SAR-20347 dose-dependently (1 nM-10 μM) inhibited JAK1 and/or TYK2 dependent signaling from the IL-12/IL-23, IL-22, and IFN-α receptors. In vivo, TYK2 mutant mice or treatment of wild type mice with SAR-20347 significantly reduced IL-12 induced IFN-γ production and IL-22-dependent Serum Amyloid A (SAA) to similar extents, indicating that in these models, SAR-20347 is probably acting through inhibition of TYK2. In an imiquimod-induced psoriasis model, the administration of SAR-20347 led to a striking decrease in disease pathology, including reduced activation of keratinocytes, and proinflammatory cytokine levels compared to both TYK2 mutant mice and wild type controls. Taken together, these data indicate that targeting both JAK1 and TYK2-mediated cytokine signaling is more effective than TYK2 inhibition alone in reducing psoriasis pathogenesis.